(untitled) (Journal of Biomedical Investigation, 2008)
The presence of dematiaceous fungi in 200 samples of soil collected from 4 different villages located in South-Eastern Nigeria were investigated. Using the pour plate method, the samples where cultured in Saboraud dextrose agar with 0.05mg/ml of chloramphenicol and incubated at room temperature. Identification of isolates was by slide culture technique and the following dematiaceous fungi were identified at different proportions; Madurella grisea 20 (43%), Fonsecaea dermatitidis 10 (21.7%), Cladosporium werneckii 10 (21.7%), Madurella mycetomi 5(10.8%), and Leptosphaeria senegalensis 1 (2.17%). Loamy soil yielded the highest number of varients of dematiaceous fungi. Madurella grisea and Fonsecaea dermatitidis were pathogenic for laboratory mice when injected subcutaneously. The findings of several dematiaceous fungi in soil samples in these villages may represent possible pattern of infections in humans since people residing in the study area were rural farmers.